Work During Non-Work Time of Public Employees - Špela Mar; Danijela Sokolić; Jernej Buzeti (Central European Public Administration Review)
Purpose: Employees and their work during non-work time are affected by technology development, societal changes and other factors that have an inherent impact on the employees’ attitude towards work during nonwork time. The purpose of this article is to provide an overview of the upto- date research on employees performing work during non-work time. Design/Methodology/Approach: The main methodological approach used in the article is a systematic literature review of 18 scientific articles found in citation databases in WOS, Scopus, etc. The collected literature is relevant as it encompasses both quantitative and qualitative analyses to gather insights on performing work during non-work time. Findings: The results imply that work during non-work time is a growing phenomenon among employees and public employees are no exception. Regarding the socio-demographic groups affected, findings indicate that work during non-work time is particularly common for employees in managerial positions and for professionals in education, health and police services, as well as for employees engaged in remote work. They also confirm that employees work during non-work time at different times of the day, at weekends, and during their annual and sick leave. Practical Implications: The article is especially relevant for public employees due to increased use of information and communication technology. As such, they are also exposed to intensifying work-related expectations and requests/pressures for flexible work arrangements. Originality/Value: The originality of the topic is reflected in the underrepresentation of scientific research on the performance of work during non-work time among public employees.